Sum-rates of radio-over-fiber small cell networks and massive MIMO for indoor communications - Wang, Q. (Institute of Electrical and Electronics Engineers Inc., 2016)
Small cell networks (SCN) and massive MIMO are both promising techniques for improving the network capacity. In this paper, we consider applying both concepts for indoor communications based on a radio-over-fiber (RoF) infrastructure. We give a comparison of the achievable sum-rates using the same system configurations which include the same set of active antennas and the same power constraints. The sum-rates are further optimized based on Geometric Programming, under both sum power constraint (SPC) and per antenna power constraint (PAPC). The numerical results indicates that both SCN and Massive MIMO offers a high network capacity. The capacity can be significantly increased when the number of antennas is a few times larger than the simultaneously served mobile stations (STAs). Massive MIMO performs much better provided that the inter-stream interference (ISI) can be canceled by the precoding techniques such as zero-forcing (ZF). However, with maximum ratio transmission (MRT), the performance of massive MIMO is poorer than SCN.